Developing Islamic Economics Research Opportunities: An Analysis from Admittance-Seeking Social Movement Theory Perspective - Ulfi, Izzani; Syahrul Mubarrok, Ujang; Sawarjuwono, Tjiptohadi; Hendratmi, Achsania (Program Studi Ekonomi Islam Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Syarifuddin Lumajang, 2023)
This research aims to determine a new research topic for Islamic economics based on the evolution of the admittance-seeking social movement (ASSM) theory. The evolution of the admittance-seeking social movement (ASSM) theory, which lasted for 35 years, started from strategic management science before spreading to other fields. Therefore, it is prospective to analyze its development and determine the right research opportunities utilized by Islamic economics. The bibliometric analysis was used in this research to describe the characteristics of its development while content analysis was used to determine the research opportunities for future Islamic economics. This research is useful for Islamic economics academics by showing new research topics for scientific advancement. The result shows that there were three main research topics namely assessing the field, research mapping, and Islamic economic movement. This study also offers future research questions derived from each research topic. Based on the authors' knowledge, this is the first research carried out to analyze the ASSM theory development and show research opportunities for Islamic economics based on the evolution of ASSM theory.